DESIGNING ENGLISH LEARNING MATERIALS FOR HOSPITALITY STUDENTS USING KURIKULUM MERDEKA IN VOCATIONAL SCHOOLS - Wahyudi, Imam (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
The English language course in vocational high schools proficiency is a requirement for hospitality employees to serve international guests. Therefore, it is necessary to provide (SMK) with a hospitality major is essential, as English English materials that are relevant to the development of the hospitality industry. This study aims to develop English instructional materials for hospitality students based on the Kurikulum Merdeka at SMK PGRI 1 Ngawi. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants in this study were 34 tenth-grade hospitality students at SMK PGRI 1 Ngawi. The results of the study produced an English module relevant to the hospitality industry. Furthermore, the developed English module was shown to increase students' motivation and competency in the learning process